2014
DOI: 10.1186/s13068-014-0129-3
|View full text |Cite
|
Sign up to set email alerts
|

A truncated form of the Carbon catabolite repressor 1 increases cellulase production in Trichoderma reesei

Abstract: BackgroundRut-C30 is a cellulase-hyperproducing Trichoderma reesei strain and, consequently, became the ancestor of most industry strains used in the production of plant cell wall-degrading enzymes, in particular cellulases. Due to three rounds of undirected mutagenesis its genetic background differs from the wild-type QM6a in many ways, of which two are the lack of a 83 kb large sequence in scaffold 15 and the partial lack of the gene encoding the Carbon catabolite repressor 1 (CREI). However, it is still unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 36 publications
(44 reference statements)
2
66
0
1
Order By: Relevance
“…In T. reesei Rut-C30, three mutations have been well studied: one is a truncation in the cre1 gene, which renders this strain carbon catabolite depressed [23]; another mutation leads to a frameshift mutation in the glycoprotein processing β-glucosidase II encoding gene [27]; the last mutation lacks a 83-kb (29 gene-encoding in the scaffold 15) region [28]. Interestingly, Rut-C30 and PC-3-7 strains, which originate from two mutation branches, possess the mutated CRE1 [6,22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In T. reesei Rut-C30, three mutations have been well studied: one is a truncation in the cre1 gene, which renders this strain carbon catabolite depressed [23]; another mutation leads to a frameshift mutation in the glycoprotein processing β-glucosidase II encoding gene [27]; the last mutation lacks a 83-kb (29 gene-encoding in the scaffold 15) region [28]. Interestingly, Rut-C30 and PC-3-7 strains, which originate from two mutation branches, possess the mutated CRE1 [6,22].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the mutation in CRE1 is common in such high cellulasesecreting mutants and corresponds with a partial release from carbon catabolite repression. Mello-de-Sousa et al [23] indicated that the truncated CRE1 contributes more to the Rut-C30 phenotype than the deletion of 29 genes encoded in the scaffold 15. But lack of the full version of CRE1 in Rut-C30 does not completely explain its hyperproduction of cellulase [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes were selected by direct searching for SNF2, ISW1, ISW2, INO80, CDH1, RSC8 (the most prominent chromatin remodelling-related proteins characterized in yeast) in the T. reesei genome database [39]. Additional candidate genes were obtained by using BLASTp (basic local alignment search tool) search in the NCBI database employing respective S. cerevisiae sequences as baits to identify similar sequences in filamentous fungi.…”
Section: Selection Of Investigated Genes Encoding Chromatin Remodellimentioning
confidence: 99%
“…Despite the evidence that CRZ1 and Ca 2+ may improve holocellulases expression, these results were obtained when the industrial strain of T. reesei RUT-C30 was evaluated in different environmental conditions. Yet, this strain harbors a deletion of approximately 85 kilobases (kb) from T. reesei’s genome which includes the cre1 locus, resulting in phenotypes that are independent on CRE1-mediated influence [34,35]. Regarding, the role of CRZ1 and Ca 2+ have not been investigated in wild type strain of T. reesei (QM6a), which harbors the full set of regulatory components into its genome.…”
Section: Introductionmentioning
confidence: 99%